The sustainable forest and the new forest economy - Travers, Ray; Homer, Edward; Inside Edge Film Inc. (Canada : Inside Edge Film Inc., 2003)
Three programs about alternative approaches to the forest and the forest economy. The first segment examines how all systems in the forest interact and features Merve Wilkinson, who has devoted most of his life to promoting selective logging in his Wildwood Forest. Part 2 looks at calculating the volume of timber to be harvested in a forest to be selectively logged as well as in a second-growth forest. Part 3 explores certification of ecological logging practices in a visit to Al Hopwood's woodlot, one of the first in BC to be certified by the Forest Stewardship Council
Part One. The sustainable forest - Part Two. Harvesting the timber - Part Three. Eco certification and the new forest economy
Production manager, Lee Homer ; Music, Brian Robbins and Allen Fleet
Narrator : Licastro
Keywords: Sustainable forestry -- British Columbia -- Vancouver Island; Forest conservation -- British Columbia -- Vancouver Island; Forest management -- British Columbia -- Vancouver Island; Logging -- British Columbia -- Vancouver Island